The talar morphology of a hypochondroplasic dwarf: A case study from the Italian Late Antique period. (22nd December 2021) - Sorrentino, Rita; Carlson, Kristian J.; Figus, Carla; Pietrobelli, Annalisa; Stephens, Nicholas B.; DeMars, Lily J. D.; Saers, Jaap P. P.; Armando, Jessica; Bettuzzi, Matteo; Guarnieri, Tiziana; Oxilia, Gregorio; Vazzana, Antonino; et al.
Abstract: This project aims to test whether geometric morphometric (GM) and trabecular analyses may be useful tools in identifying talar characteristics related to hypochondroplasia. We quantified the external and internal talar morphology of a hypochondroplasic dwarf (T17) from Modena (northern Italy) dated to the sixth century AD. External talar morphology of T17 was compared with a broad sample of modern human tali ( n = 159) using GM methods. Additionally, a subsample of these tali ( n = 41) was used to investigate whole talar trabecular changes in T17. Our results show that GM and trabecular analyses identify a combination of traits linked to the dwarfing disorder of hypochondroplasia. These traits include decreased scaled talar dimensions compared with normal‐sized individuals, presence of an accessory antero‐lateral talar facet, high bone volume fraction, and high anisotropy values throughout the entire talus. In our case study, hypochondroplasia does not appear to substantially modify external talar morphology probably due to the fast growth of the talus. We suggest that small talar dimensions are associated with hypochondroplasia. An antero‐lateral talar facet may result from the talus and calcaneus coalition (i.e., talocalcaneal abnormal bridging) possibly related to an everted foot posture that was limited by overgrowth of the fibula. We suggest that high talar trabecular density and strut orientation provide insights into pathological development of the trabecular plates in T17. Finally, our study suggests that high talar trabecular density and strut orientation, and small talar dimensions, may be added as possible concomitant talar hallmarks for hypochondroplasia.